Morphological adaptations in response to chronic exercise across musculoskeletal tissues: A systematic review - Felix León; Andres Mestre; Lorelu Priego; Juan Carlos Vera (Universidad de Costa Rica, 2023)
To date, there is no systematic review that summarizes the morphological adaptations of the musculoskeletal system in response to chronic exercise. This systematic review selected original articles published in English between 2000 and 2020, with a clear exercise intervention and presenting a morphological change in the tissue under study, and coveringhuman participants irrespective of age, gender or health condition. In total, 2819 records were identified. After removal of duplicates, title and abstract screening and full-text review, 67 records were included in the final analysis (6 for inter-vertebral disc, 6 for cartilage, 36 for bone, 2 for ligament, 9 for tendon and 7 for muscle). The most used interventions were aerobic, resistance, and plyometric exercise. Population ranged from children and healthy active people to individuals with a health condition. In conclusion, as a response to chronic exercise there are morphological adaptations in the tissues of the musculoskeletal system which vary from increased stiffness to an increase in cross-sectional area. Although tissues can adapt, several questions still linger, such as optimal dose and type of exercise, whether adaptations can occur in an injured tissue, and functional implications of these adaptations. Future research should address these questions.